Harnessing Social Media for Independent Learning: Insights from Higher Education Students - Lokollo, Lamberthus J. (Journal of Ecohumanism, 2025)
The utilisation of social media has changed the educational landscape by providing a flexible and innovative platform for students’ self-directed learning. This study aims to explore the impact of social media as a source of self-directed learning on undergraduate students at the Faculty of Teacher Training and Education, Pattimura University, Indonesia. Using a quantitative-descriptive approach, data was collected from 166 students through a structured questionnaire. The results showed high usage of social media for learning, with platforms such as YouTube, Instagram, and WhatsApp being the most frequently used. Students utilise social media to complete academic tasks, expand their knowledge, and improve their digital competence, reflecting the potential of social media as an adaptive and effective learning tool.This research highlights the role of social media in supporting the principles of andragogy and lifelong learning, and identifies various benefits, including collaboration, creativity and problem-solving. However, it also reveals challenges such as distraction and the validity of online information.The results provide practical recommendations for educational institutions to optimise the use of social media in the learning process, including through digital literacy training and integration into the curriculum. The findings offer important insights for the development of innovative digital education that supports students’ learning needs in the modern era.